2019
DOI: 10.1007/s10811-019-01793-x
|View full text |Cite
|
Sign up to set email alerts
|

Twine selection is essential for successful hatchery cultivation of Saccharina latissima, seeded with either meiospores or juvenile sporophytes

Abstract: The predominant method used for the cultivation of European kelp involves seeding onto twine spools. The selection of a suitable twine is essential. In four experiments, synthetic and natural polymer twines were seeded with either meiospore or juvenile sporophytes of Saccharina latissima. Development was monitored over both the hatchery and outplanting phase at an experiment seaweed farm, Scotland, UK. Twisted twine seeded with meiospores gave 37 ± 21% higher biomass yield than the braided form, despite 46 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The rope structure and material used for seeding have proven to have a large impact on the harvesting yield. Twisted ropes have shown significantly better performance than braided ropes for both spore and juvenile sporophyte seeding (Kerrison et al 2019). The spores and gametophytes were seeded on a twisted nylon string (⌀ 1.2 mm and wound around ⌀ 18 mm twisted rope when deployed), while the treatments using a binder were seeded directly on a braided rope (⌀ 18 mm, AlgaeRope).…”
Section: Direct Seedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The rope structure and material used for seeding have proven to have a large impact on the harvesting yield. Twisted ropes have shown significantly better performance than braided ropes for both spore and juvenile sporophyte seeding (Kerrison et al 2019). The spores and gametophytes were seeded on a twisted nylon string (⌀ 1.2 mm and wound around ⌀ 18 mm twisted rope when deployed), while the treatments using a binder were seeded directly on a braided rope (⌀ 18 mm, AlgaeRope).…”
Section: Direct Seedingmentioning
confidence: 99%
“…This method can be advantageous as the use of incubation facilities might be shortened by several weeks or, in the case of direct seeding, omitted completely. The use of a binder to attach spores, gametophytes or sporophytes to the substrate is preferred by several commercial farmers and in research projects (Mols-Mortensen et al 2017;Bak et al 2018;Kerrison et al 2018Kerrison et al , 2019. Recent experiments have shown that a binder method of cultivation is not only as effective as traditional methods but also can be 100 times more space-efficient during the laboratory phase (Kerrison et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Their firm initial attachment allows the sporophytes to immediately tolerate high wave energy. The physical and chemical characters of the twine dictate how strongly the juveniles are attached, and so can influence the final yield (Kerrison et al 2019b ). As the sporophytes mature, their developing holdfasts spread onto the carrier rope and will mechanically interlock around the rope and neighbouring holdfasts (pers.…”
Section: Discussionmentioning
confidence: 99%
“…To this day, there is no clear consensus on which cultivation method is best suited for large-scale kelp aquaculture. Kelp aquaculture is still being practiced using two fundamentally different cultivation methods (Kerrison et al 2019;Goecke et al 2020), which are categorized here as the controlled-and uncontrolled reproductive methods (Ebbing et al 2021). The uncontrolled reproductive method (URM) is characterized by releasing substantial amounts of zoospores in large tanks that are filled with twine rope.…”
Section: Introductionmentioning
confidence: 99%